Cathedrals and Crisis in Seventeenth-Century Castile: The Case of Seville and Its Church of the Sagrario. Issue 1 (29th December 2014) - d'Arcy, Sing
Abstract : When it came time for the critics and historiographers of the late eighteenth and early nineteenth centuries to write the grand narrative of Spanish architecture, the decadence of the Habsburg monarchy, its economy and its society, paralleled the decline of the noble art itself. The completion of the Escorial in 1584 loomed more like an enormous granite epitaph for Spanish architectural production than the promise of a New Jerusalem. For seventeenth-century architects and theoreticians, such as Fray Lorenzo de San Nicolás, and nineteenth-century commentators, such as Agustín Ceán Bermúdez, the introduction of painters, joiners, silversmiths and other guilds into the realm of architectural design was seen as the principal corruptive force leading to the unpardonable horrors of the Baroque. These negative topoi have, in many cases, found their way into the contemporary historiography of Spanish architecture of the period, typically depicted as all surface and no space, relegating it to a place of lesser importance.